Lifestyle vs Transplantation Therapies Aiding in Pancreatic Beta Cell Protection for Type 1 Diabetes - Stierli, Micah; Abdalbari, Ali; Pore, Arya (Journal of Student Research, 2023)
Pancreatic beta cells highly influence the level of insulin within the body. This being due to the beta cell’s ability to create and regulate the production of insulin (the hormone that manages blood sugar extent). Unfortunately, the increasing death rate of these cells has complicated insulin independence for people with type 1 and type 2 diabetes. Type 1 diabetes (T1D) continues to be a serious concern considering the globally growing incidence rate and the regard that there is no currently confirmed cure. However, multiple new cellular therapies have been explored and evaluated to aid in beta cell regeneration strategies. This literature review focuses specifically on commonly practiced beta cell regeneration therapies for type 1 diabetes. These therapeutic approaches were divided to fit into one of two categories, these categories being cellular reproduction and cell replacement which will be further expanded on throughout this article. Topics discussed within the work aim to exhibit a brief overview of the type 1 diabetes patient population, beta cell pathophysiology, and cover concepts regarding methods of measuring procedural success. The majority of this article will be centered around commonly practiced clinical strategies involving pancreas/islet cell transplantation and therapeutic lifestyle approaches. All this is concluded with a general comparison of typical beta cell therapies.